Linkages Between Breast Milk Substitute Limiting Interventions and Breastfeeding Outcomes: A Scoping Review (Journal of Science and Technology, 2025)
Background: The initiation of infants to human milk within the first hour of delivery, exclusive breastfeeding for 180 days and continued breastfeeding up to 24 months or beyond are standard breastfeeding recommendations. However, globally, the majority of infants do not experience optimal breastfeeding for many reasons including the unethical and inappropriate commercial marketing strategies that expose children to breast milk substitutes (BMS). Research Aim: To identify and categorise published interventions that promote, protect and support breastfeeding while limiting exposure to and use of BMS, globally.Methods: Arksey and O’Malley’s (2005) scoping review process guided this review. An initial search of peer-reviewed health-related literature databases was updated by searching through CINAHL, Google Scholar, Pubmed, PSYCHINFO, and SCOPUS. WHO and UNICEF’s websites. Keywords used included human milk, breastfeeding, breast milk substitute, formula feeding and interventions. Full-text, peer-reviewed research articles published in the English language between 1990-2022 were eligible for the review. Thematic data analysis was done.Results: We identified 447 records and of these, there were seven articles that were eligible for inclusion in this review. Seven themes were discovered as key intervention strategies to facilitate breastfeeding and limit BMS use, globally. The interventions included health worker training programs and educational strategy; implementation and revitalisation of the Baby- Friendly Hospital Initiative; formula payment policy; diaper bag donation (not containing BMS); government-owned breastfeeding programs; enforcement of the International Code of Breastmilk Substitutes and implementation of other enabling factors.Conclusion: Globally, there are few facility-and community-based strategies to mitigate the marketing and use of BMS. The adoption of the identified BMS interventions can be leveraged to protect, promote and support optimal breastfeeding.